1996
DOI: 10.1037/0278-6133.15.5.371
|View full text |Cite
|
Sign up to set email alerts
|

Increasing condom use: Evaluation of a theory-based intervention to prevent sexually transmitted diseases in young women.

Abstract: A multicomponent intervention to increase condom use in sexually active young women was designed, implemented, and evaluated in a randomized experiment. Participants were 198 unmarried female college students (mean age = 18.6 years) who received a 1-session condom promotion intervention or a control (stress management) intervention. The condom promotion intervention led to increased self-reported condom use up to 6 months following intervention as well as positive changes in perceived benefits of condom use, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
161
0
13

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(178 citation statements)
references
References 73 publications
3
161
0
13
Order By: Relevance
“…Both theories have shown a great ability to predict condom use (Albarracin, Kumkale, & Johnson, 2004;Basen-Engquist & Parcel, 1992;Bryan, Aiken, & West, 1996;Fisher, Fisher, & Rye, 1995;Jemmott, Jemmott, & Hacker, 1992;Jemmott III et al, 2007). The meta-analysis by Sheeran, Abraham, and Orbell (1999) concluded that there is a medium to strong relationship between intentions to use condoms and actual behavior.…”
Section: Theoretical Rationalementioning
confidence: 99%
“…Both theories have shown a great ability to predict condom use (Albarracin, Kumkale, & Johnson, 2004;Basen-Engquist & Parcel, 1992;Bryan, Aiken, & West, 1996;Fisher, Fisher, & Rye, 1995;Jemmott, Jemmott, & Hacker, 1992;Jemmott III et al, 2007). The meta-analysis by Sheeran, Abraham, and Orbell (1999) concluded that there is a medium to strong relationship between intentions to use condoms and actual behavior.…”
Section: Theoretical Rationalementioning
confidence: 99%
“…A number of HIV prevention interventions have been guided, at least in part, by the TPB's emphasis on the importance of strengthening perceptions of control in efforts to promote performance of preventive behaviors (see, for example, Basen-Enquist,lX6 Bryan et a1.. 66 Jemmott and J e m m~t t l~~) .…”
Section: Fundamental Assumptionsmentioning
confidence: 99%
“…For example, the health belief model (Becker, 1974;Rosenstock, 1974) posits in part that increasing perceptions of vulnerability to HIV infection should increase precautionary behavior. Yet a recent quantitative synthesis found that chronic perceived vulnerability to HIV infection in members of high-risk groups is insufficient to motivate protective actions (Gerrard, Gibbons, & Bushman, 1996; but see Bryan, Aiken, & West, 1996). The limited support for the perceived-risk hypothesis suggests a need for other behavioral models of HIV-risk-related behavior.…”
mentioning
confidence: 99%